Quality of manufacturing of gears from sparingly alloyed steel at all stages of technological conversion - S. P. Rudenko; A. I. Valko; P. I. Papkovski; S. G. Sandomirski; P. G. Karpovich (Литьë и металлургия, 2022)
The advantages of sparingly alloyed steels for the manufacture of large-module gears are substantiated. A test output quality control of the manufacture of gears from rolled new structural sparingly alloyed steel 21ХГНМБА (21KhGNMBA) was carried out at all stages of technological conversion in the conditions of serial production. The efficiency of the developed technological processes of preliminary heat treatment of workpieces and chemical-thermal treatment of gears is shown. A significant reduction in the labor intensity of these processes is achieved in comparison with the processes of chemical-thermal treatment of steels with a high nickel content. Recommendations are given on the choice of an abrasive tool for grinding surface-hardened gears made of economically alloyed steel.